Shugendō: Pilgrimage and Ritual in a Japanese Folk Religion - Andrea K. Gill (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
The religion of Shugendō has no shrines and it has no temples. It only has the liminality of the mountains; a space that is viewed in Japan as being ground that only gods, demons, and ghosts may set foot on. But the Yamabushi are not human, gods, or even demons. Instead they are believed to be living Buddhas, rare people that, through practice in the secluded mountains, have become privy to sacred knowledge that has awakened them to their internal Buddha nature, to borrow the words of Kukai, “in this very lifetime”. One of the defining features of Shugendō is the relationship that is formed between man, gods, and nature in the context of the sacred mountain (Grapard, 1994). Another feature found strongly in Shugendō is the role that the Yamabushi play in the communities surrounding their sacred mountains.
Keywords: Shugendō; Japan; Religion; Folklore